The immune modulatory peptide FhHDM‐1 secreted by the helminth Fasciola hepatica prevents NLRP3 inflammasome activation by inhibiting endolysosomal acidification in macrophages. Issue 1 (28th September 2016) - Alvarado, Raquel; To, Joyce; Lund, Maria E.; Pinar, Anita; Mansell, Ashley; Robinson, Mark W.; O'Brien, Bronwyn A.; Dalton, John P.; Donnelly, Sheila
Abstract : The NLRP3 inflammasome is a multimeric protein complex that controls the production of IL‐1β, a cytokine that influences the development of both innate and adaptive immune responses. Helminth parasites secrete molecules that interact with innate immune cells, modulating their activity to ultimately determine the phenotype of differentiated T cells, thus creating an immune environment that is conducive to sustaining chronic infection. We show that one of these molecules, FhHDM‐1, a cathelicidin‐like peptide secreted by the helminth parasite, Fasciola hepatica, inhibits the activation of the NLRP3 inflammasome resulting in reduced secretion of IL‐1β by macrophages. FhHDM‐1 had no effect on the synthesis of pro‐IL‐1β. Rather, the inhibitory effect was associatedwith the capacity of the peptide to prevent acidification of the endolysosome. The activation of cathepsin B protease by lysosomal destabilization was prevented in FhHDM‐1‐treated macrophages. By contrast, peptide derivatives of FhHDM‐1 that did not alter the lysosomal pH did not inhibit secretion of IL‐1β. Wepropose a novel immunemodulatory strategy usedby F. hepatica, whereby secretion of the FhHDM‐1 peptide impairs the activation of NLRP3 by lysosomal cathepsin B protease, which prevents the downstream production of IL‐1β and the development of protective T helper 1 type immune responses that are detrimental to parasite survival.—Alvarado, R., To, J., Lund, M. E., Pinar, A., Mansell, A., Robinson, M. W., O'Brien, B. A., Dalton, J. P., Donnelly, S. The immune modulatory peptide FhHDM‐1 secreted by the helminth Fasciola hepatica prevents NLRP3 inflammasome activation by inhibiting endolysosomal acidification in macrophages. FASEB J. 31, 85–95 (2017) www.fasebj.org